Eikonal Blog


Expansions of the exponentials of the sums of matrices

Richmond’s formula #1: e^{t(A+B)} = e^{tA}e^{tB} + \sum_{r=0}^\infty E_r t^r, where:

  • E_{r+1} = \frac1{r+1}\left((A+B)E_r+[B,F_r]\right) \ with E_0=E_1=0,
  • F_{r+1} = \frac1{r+1}(A F_r + F_r B) \ with F_0=1.

Richmond’s formula #2: e^{t(A+B)} = \frac12(e^{tA}e^{tB}+e^{tB}e^{tA}) + \sum_{r=0}^\infty E'_r t^r, where:

  • E'_{f+1} = \frac1{r+1}((A+B)E'_r+\frac12[B,F_r]+\frac12[A,F^{*}_r]) \ with E'_0=E'_1=E'_2=0, and where F_r‘s are the same as in the Richmond’s formula #1.
  • Following bounds are valid: ||E'_r|| < \frac1{(r-1)!} (||A||+||B||)^r.

Note that the exponential generating function {\cal F}(z):\equiv \sum_{r=0}^\infty \frac{z^r}{r!} F_r satisfies the second order ODE: \partial_z (z\partial_z {\cal F}(z)) = A{\cal F}(z)+{\cal F}(z)B.

Source: T1269 = A.N.Richmond “Expansion for the exponential of a sum of matrices”; Int. Journal of Control (issue and year unknown).

Blog at WordPress.com.